2004
DOI: 10.1002/polb.20311
|View full text |Cite
|
Sign up to set email alerts
|

Side‐chain crystallization behavior of graft copolymers consisting of amorphous main chain and crystalline side chains: Poly(methyl methacrylate)‐graft‐poly(ethylene glycol) and poly(methyl acrylate)‐graft‐poly(ethylene glycol)

Abstract: Graft copolymers consisting of amorphous main chain, poly(methyl methacrylate) (PMMA), or poly(methyl acrylate) (PMAc), and crystalline side chains, poly(ethylene glycol) (PEG), have been prepared by copolymerization of PEG macromonomers with methyl methacrylate or methyl acrylate (MMAx or MACx, respectively). Because of the compatibility of PMMA/PEG and PMAc/PEG, from small-angle X-ray scattering results, the main and side chains in graft copolymers were suggested to be homogeneous in the molten state. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 30 publications
4
31
0
Order By: Relevance
“…But the PEG segments did not recrystallize during cooling in any of our polymers (Figure 4), even when cooled at 1 °C/min; the PEG blocks in polymers such as 15 and 30% PEG 1k DTE and 30%PEG 1k I 2 DTE should have crystallized during cooling at ~ 20 °C below T m as observed in other copolymers [7]. PEG blocks did crystallize when the samples were aged (~ 3 days).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…But the PEG segments did not recrystallize during cooling in any of our polymers (Figure 4), even when cooled at 1 °C/min; the PEG blocks in polymers such as 15 and 30% PEG 1k DTE and 30%PEG 1k I 2 DTE should have crystallized during cooling at ~ 20 °C below T m as observed in other copolymers [7]. PEG blocks did crystallize when the samples were aged (~ 3 days).…”
Section: Resultssupporting
confidence: 58%
“…The influence of PEG depends on whether the polymer is a blend [56], a graft [1, 7], a diblock [810] or a segmented block [11] copolymer. Segmented block copolymers with PEG as one the blocks have been studied in aqueous solution [1214], gel [15], and in the solid phase [10, 1617].…”
Section: Introductionmentioning
confidence: 99%
“…For graft copolymers, despite their potential importance in industry, only limited studies on the phase behavior and morphology have been reported 2, 5–14. We can expect that in semicrystalline graft copolymers containing crystallizable block chains, the morphology by microphase separation in the molten state before crystallization will be an important factor influencing the crystallization behavior, as reported for semicrystalline diblock copolymers.…”
Section: Introductionmentioning
confidence: 87%
“…The phase behavior and microphase separation of multicomponent polymers, such as block copolymers and graft copolymers, have attracted much attention because of their ability to form a self‐assembled ordered structure with a nanometer‐sized periodicity 1–14. Diblock copolymers consisting of two incompatible amorphous polymers have been most widely investigated with experimental and theoretical approaches 1, 3, 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation